2012
DOI: 10.3892/ol.2012.669
|View full text |Cite
|
Sign up to set email alerts
|

Changes in leukocyte gene expression profiles induced by antineoplastic chemotherapy

Abstract: Abstract. In the present study, we studied changes in gene expression induced by chemotherapy (CT) on normal peripheral blood leukocytes (PBLs), at baseline and following three CT cycles, in order to identify which genes were specifically affected and were potentially useful as biomarkers for a personalised prognosis and follow-up. A PBL subtraction cDNA library was constructed from four patients undergoing CT with paclitaxel and carboplatin

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…These results are consistent with previous studies that have shown transcriptional effects of taxanes independently of microtubule formation (22, 23). For example, we found that nab-paclitaxel treatment results in increased expression of IL1β , which encodes a pro-inflammatory cytokine.…”
Section: Discussionsupporting
confidence: 94%
“…These results are consistent with previous studies that have shown transcriptional effects of taxanes independently of microtubule formation (22, 23). For example, we found that nab-paclitaxel treatment results in increased expression of IL1β , which encodes a pro-inflammatory cytokine.…”
Section: Discussionsupporting
confidence: 94%
“…It is one of the most common auto-antigens present in inflammatory myopathies, with one fourth of juvenile dermatomyositis (DM) patients being found positive for anti-MORC3 antibodies (Gunawardena et al, 2009). Recent clinical studies reveal elevated MORC3 expression in leukocytes following anti-cancer chemotherapy (Gonzalez-Fernandez et al, 2012). MORC3 localizes to promyelocytic leukemia nuclear bodies (PML-NBs), where it regulates p53 activity essential for cellular senescence in human and mouse fibroblasts (Mimura et al, 2010; Takahashi et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…MORC3 | ATPase | CW | histone | chromatin M icrorchidia 3 (MORC3) is a member of a new family of human ATPases. Originally identified as an autoantigen in inflammatory myopathies (1)(2)(3), it has since been linked to other autoimmune disorders, Down syndrome, and cancer (4)(5)(6)(7). Studies using mouse models show that knockout of Morc3 is perinatally lethal, and partial loss of Morc3 results in changes in bone calcium homeostasis and up-regulation of inflammatory pathways (8).…”
mentioning
confidence: 99%